Peran Content Creator Dalam Membangun Bisnis Startup Pada RM Inkubasi di RM Synergy (Current Research in Education: Conference Series Journal, 2023)
Covid-19 has an impact on people's lives in all aspects, including the economy in Indonesia. One of the sectors affected is the business sector. Not a few of them have resilience or resiliency. New Normal is the economic recovery of people who have to adapt to new life habits. Incubation provides a platform for creating startup business content on social media so that the development of the business sector gets a stable economy. Social media is the main pillar in the delivery of information and can be used to introduce products and support business activities. In optimizing social media, it is necessary to have a content creator for startup business content creation in order to build Brand Awareness, Engagement, Keyword and SEO (Search Engine Optimization) on Social Media. RM Incubation as a place to develop the current business. Based on research conducted using survey survey methods and questionnaires, 98% of respondents stated that social media can be useful in the business sector. Then in packaging the content must be attractive and in accordance with the criteria you want to aim for, even those that are the target of attracting the interest of the audience in order to develop the brand.